KEANEKARAGAMAN DAN PEMANFAATAN TUMBUHAN DI PULAU NUSAKAMBANGAN - CILACAP, JAWA TENGAH - Setyowati, Francisca Murti (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2005)
Among some natural reserves in Java Island and the vicinity only theNusakambangan Natural Reserve, which might be characterized as the last lowland forest in this region. In fact however, there is only in eastern and western part of Nusakambangan Island, which remain covered with relatively undisturbed forest. Survey-explorative methods which including interview and direct field observation was applied in order to collect data of useful plant. There are 253 species of plant using by people in surrounding Cilacap for their daily necessitate such as foodstuff, charge coal, traditional remedy etc. Some plant species, which was categorized as in risk category, dominate, potential and have a good prospect, will be discussed in this paper.